Does internet development improve green total factor energy efficiency? Evidence from China - Wu, Haitao; Hao, Yu; Ren, Siyu; Yang, Xiaodong; Xie, Guo (Energy policy, 2021)
Information and communication technology supported by the internet has become an important driving force that promotes the intelligent development of environmental governance in China. Using Chinese provincial panel data for the period 2006–2017, this study investigates whether the internet has improved China's green total factor energy efficiency (GTFEE) using a dynamic spatial Durbin model, mediation effect model and dynamic threshold panel model. The empirical results indicate that the GTFEE has a significant positive spatial correlation. Internet development can not only directly improve local GTFEE but also improve GTFEE in neighboring regions. After accounting for potential endogeneity, this conclusion is still valid. Meanwhile, internet development can indirectly improve regional GTFEE by reducing the degree of resource mismatch while enhancing GTFEE by improving regional innovation capabilities and promoting industrial structure upgrades. In addition, the regression results of the dynamic threshold model show that there is a nonlinear relationship between the influence of the internet development and GTFEE. Specifically, due to an increase in the degree of labor resource mismatch and capital resource mismatch, the impact of the internet on GTFEE has gradually decreased, and this effect has gradually increased with the improvement of regional innovation capabilities and the industrial structure. •Green total factor energy efficiency (GTFEE) of 30 provinces in China is estimated.•Influence of internet development on GTFEE efficiency is quantitatively investigated.•A spatial-Durbin model that accounts for potential spatial spillover effects is employed.•Internet development can significantly improve GTFEE, but the relationship is nonlinear.•Resource mismatch, technological innovation and industrial upgrading may affect GTFEE.